Multilateral maritime security cooperation in the Indian Ocean region: status and prospects. Issue 1 (2nd January 2016) - Upadhyaya, Shishir
ABSTRACT: This article is based on a presentation made by the author at the Indian Ocean Regional Association Dialogue 2015 (a Track 1.5 initiative) at Perth in September 2015. It provides an overview of the extant sub-regional and regional multilateral maritime security cooperation mechanisms in the Indian Ocean Region to highlights the lessons learnt. It argues that while the sub-regional organisations seem to be working well, the regional organisations need to evolve in keeping with the changed maritime environment of the 21st century.